Drug eluting hydrogels design, synthesis and evaluation - Ahrenstedt, Lage (Department of Surgery, 2014)
Hydrogels have successfully proved themselves useful for drug delivery applications and several delivery routes have been developed over the years. The particular interest in this work was to design, synthesise and evaluate in situ forming drug eluting hydrogels, which have the potential to ameliorate the healing of cardiovascular diseases.